Growth and production of cucumber (Cucumis sativus L.) that cultivaed using various types of mulch and different doses of goat manure - Futichat A’mila Khoirunnisa; Eny Fuskhah (Talenta Publisher, 2019)
Improvement of cultivation techniques and increasing soil fertility through the use of fertilizersneed to be considered to produce maximum cucumber plant growth and production. Theresearch was aimed to examine the response of the growth and production of cucumber plantsthat cultivated using various types of mulch and different doses of goat manure. The researchwas conducted on March - June 2019 at the Merbuh Village, Singorojo sub-district, Kendaldistrict of Central Java Province. A block randomized design factorial pattern 3 x 4 with threereplications was used throughout the experiment. The first factor consisted of treatment withoutmulch (M0), rice straw mulch (M1) and black silver plastic mulch (M2). The second factorconsisted of 4 levels of Nitrogen doses including P0 = Nitrogen, phosphorus, and potassium(NPK) recommendation for cucumber plant 160 kg N/ha; P1 = 177 kg N/ha; P2 = 354 kg N/ha;P3 = 531 kg N/ha respectively equal to 0, 10, 20, and 30 tons of manure/ha. The data obtainedwere analyzed using analysis of variance (ANOVA), and a further test was carried out on theparameters that showed a significant difference in the mean values of the treatment using theDuncan test. The results showed that the treatment of silver black plastic mulch increased thegrowth and production of cucumber plants. The treatment of goat manure at a dose of 10tons/ha had been able to increase all parameters and goat manure with a dose of 30 tons/hagave high results on all parameters of cucumber plants compared to that of the control. Thetreatment of black silver plastic mulch with a goat manure dose of 30 tons/ha gave high resultsin the number of fruit parameters.